PENTINGNYA SINERGITAS KECERDASAN IQ, EQ, dan SQ SERTA OPTIMALISASI EMOTIONAL INTELLEGENCE SEBAGAI ROLE MODEL DALAM KEPEMIMPINAN PUBLIK - Susilawati, lena; Purwanda, Eka (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
A great nation requires competent leaders who possess Intelligence Quotient (IQ), Emotional Intelligence (EQ), and Spiritual Intelligence (SQ) in managing this great nation. The synergy of IQ, EQ, and SQ intelligences can lead leaders to achieve outstanding success. The recent leadership crises have raised concerns among many, and this should be a significant focus. This phenomenon has sparked collective awareness of the importance of seeking an ideal leader as a Role Model in leadership. The purpose of this research is to analyze the importance of the synergy of IQ, EQ, and SQ intelligences, as well as the optimization of EQ as a Role Model in public leadership. We need visionary leaders who are innovative, educated, have a strong leadership spirit, a high sense of empathy, effective communication skills, a dedication to society, a caring attitude towards the community, a moral responsibility, a commitment to God, upholding the value of honesty, and dedicating themselves when in positions for the benefit of the public. Success as a leader is evident through policies that favor the community. An exemplary leader is needed to serve as a Role Model, capable of addressing complex issues and resolving conflicts effectively. In this study, the researcher observed three public leadership figures in three different areas: the Head of Samsat Aceh Utara, the Director of BUMDes Arya Kemuning Kuningan, and the Lurah Binjonhara in Tapanuli Selatan. The researcher employed qualitative research with a descriptive and comparative approach. The conclusion of this qualitative study is that the simultaneous synergy of IQ, EQ, and SQ contributes significantly to achieving success in public leadership as a Role Model Leader. The optimization of Emotional Intelligence (EQ) is proven to be crucial in the success of the leadership of these three figures.